The role of microtubules in neutrophil polarity and migration in live zebrafish - Yoo, Sa Kan (The Company of Biologists, 2012)
Microtubules control cell motility by positively regulating polarization in many cell types. However, how microtubules regulate leukocyte migration is not well understood, particularly in living organisms. Here we exploited the zebrafish system to study the role of microtubules in neutrophil migration in vivo. The localization of microtubules was visualized in motile neutrophils using various bioprobes, revealing that, in contrast to what has been seen in studies in vitro, the microtubule organizing center is positioned in front of the nucleus (relative to the direction of migration) in motile neutrophils. Microtubule disassembly impaired attraction of neutrophils to wounds but enhanced the polarity of F-actin dynamics as measured by the distribution of stable and dynamic F-actin. Microtubule depolymerization inhibited polarized phosphoinositol 3-kinase (PI(3)K) activation at the leading edge and induced rapid PI(3)K independent motility. Finally, we show that microtubules exert their effects on neutrophil polarity and motility at least in part by the negative regulation of both Rho and Rac activity. These results provide new insight into the role of microtubules in neutrophil migration in a living vertebrate and show that the motility of these professional migratory cells are subject to distinctly different rules from those established for other cell types.